Implementation of Laparoscopic Bilateral Salpingo-Oophorectomy for Breast Cancer Patients in a Surgical Oncology Setting: A Report from Nepal - Lamichhane, Deep; Suwal, Suraj; Rana, Resham; Baral, Shweta (Nepalese Journal of Cancer, 2025)
Introduction: Breast cancer is one of the common malignancy among women in Nepal, with a rise in incidence among younger, premenopausal patients. A significant proportion are hormone receptor positive (HR+), where ovarian function suppression (OFS) remains a cornerstone of systemic therapy. Bilateral salpingo-oophorectomy (BSO) provides a permanent, compliance-free method of OFS, particularly relevant for metastatic disease, recurrence, or risk reduction in BRCA mutation carriers. Traditionally considered the domain of gynaecologists, laparoscopic BSO can also be safely performed by surgical oncologists with laparoscopic skills, thereby avoiding interdepartmental delays and maintaining continuity of care. This study reports the experience of implementing laparoscopic BSO for breast cancer patients in a surgical oncology unit. Methods: All consecutive patients undergoing laparoscopic BSO between January 2020 and December 2024 in a surgical oncology unit at Bhaktapur Cancer Hospital were included. Data were extracted from a prospectively maintained departmental database. Clinical variables, indications, perioperative details, complications, and histopathology findings were analysed. Data analysis was descriptive, using Microsoft Excel (Microsoft Corporation, Redmond, WA, USA). Results: Thirty patients underwent laparoscopic BSO, with a median age of 37 years (IQR: 32–43). The most common indications were metastatic disease (n=14), recurrence (n=8), BRCA mutation pathogenic status (n=5), high-risk disease (n=2) and progression on neoadjuvant chemotherapy (n=1). The median operative duration was 60 minutes (IQR: 53–80). There were no conversions to open surgery, reexplorations, or readmissions. The mean hospital stay was 2.6 days. Histopathological evaluation revealed ovarian metastases in six cases (20%), fallopian tube tuberculosis in one case, mature cystic teratoma in one case, and unremarkable findings in the remaining 22 patients. Conclusion: Laparoscopic BSO performed by surgical oncologists is a safe, feasible, and effective procedure in the continuum of care for breast cancer. It provides definitive ovarian suppression with low morbidity, avoids delays associated with referrals, and ensures continuity of care. These findings support the role of surgical oncologists in integrating laparoscopic BSO into comprehensive breast cancer management.